Pengaruh Perubahan Kurikulum Terhadap Pembelajaran Peserta Didik Di Sekolah Dasar - Putri Amelia Dwiyanti; Achmad Junaedi Sitika; Hanifah Surachmawardani; Mimi Mutiara; Mufti Abdul Malik; Nurhadi Muhammad Ramdani; Nadila Agustin; Putri Umairoh Umayah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Curriculum as study material is a very important tool for academic success. Curriculum changes are based on the awareness that developments and changes in social, national and state life in Indonesia cannot be separated from the influence of global changes, scientific-technical developments, as well as arts and culture. In addition, the updated curriculum reform also did not have a positive impact on the development of the quality of the 1975, 1984, 1994, 2004 (KBK), 2006 (KTSP) and 2013 curriculum. The quality of our education is still low at this time. For the world of education, the role of curriculum developers is very important to achieve better learning processes and outcomes. In this article we want to describe curriculum changes, problems of curriculum changes, the impact of curriculum changes on learning in elementary schools.